Shifting to green economy: Hype or hope for entrepreneurs into medicinal and aromatic plants? - Almeida, I.; Silva, J.; Leite, M. (Proceedings 21st EurOMA Conference, 2014)
This research aimed at finding out if rural development concerning medicinal and aromatic plants (MAP), in Portugal, was sufficiently consolidated to be considered an alternative lifestyle. Secondary data collected from a panel of 12 high-level experts enabled to picture the sector. Operations were the core knowledge area that helped to find out the implementation of the existing social platform into a technological solution to support a virtual collaborative effort among the stakeholders, as the main requirement to consolidate the sector. The required role of State was also defined as holistic, integrative, supportive, despite not-regulative, to implement a broad MAP policy.